Whistleblowing System, Competence, Morality, and Internal Control System Against Fraud Prevention on Village Financial Management in Denpasar - Sujana, I Ketut; Suardikha, I Made Sadha; Laksmi, Putu Santi Putri (E-Jurnal Akuntansi, 2020)
This study aims to test empirically the effect of the whistleblowing system, human resource competence, morality and internal control systems on fraud prevention in village financial management .  The data source used is primary data from the results of distributing questionnaires to village officials who are involved as managers of village fund allocations as many as 97 respondents.  The sampling technique was the total method or census, namely 27 Dinas Villages in Denpasar City and data analysis used multiple linear regression analysis. The results of this study indicate that the whistleblowing system has no effect on fraud prevention in village financial management. Meanwhile, human resource competence, morality, and internal control systems have a positive effect on fraud prevention in village financial management. Keywords: Whistleblowing System; Human Resource Competence; Morality; Internal Control System; Fraud .